FAKTOR-FAKTOR PRODUKSI YANG MEMPENGARUHI PENDAPATAN PENGERAJIN PADA INDUSTRI KERAJINAN KULIT DI KABUPATEN BADUNG - Tungga Dangin, I Gede Ari Bona; Marhaeni, A.A.I.N. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.07.TAHUN 2019DO - 10.24843/EEB.2019.v08.i07.p02, 2019)
The aims at this study are 1) to analyze the effect of labor, capital, technology and availability of raw materials on production, 2) the influence of labor, capital, technology, availability of raw materials and production on income and 3) the indirect influence of labor, capital, technology and availability of raw materials on income through the production of craftsmen in the leather craft industry. Sample size of this used is about 62 craftsmen in the leather craft. The results show that labor and capital have a positive and significant effect on the production of craftsmen in the leather craft. The firm that use modern technology has higher production than the firm that use traditional technology. The availability of smooth raw materials results in higher production than the substandard ones. Labor, capital and production have a positive and significant effect on the income of craftsmen in the leather craft industry. Using of modern technology generates higher income than traditional technology. The availability of raw materials that smoothly generates higher income than those that have less smooth. P roduction mediates partially the influence of labor capital, technology and availability of raw materials on the income of craftsmen in the leather craft industry.